2022
DOI: 10.3390/e24050671
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multi-Component Surrogates on the Performances, Pollutants, and Exergy of IC Engines

Abstract: Even though there is a pressing interest in clean energy sources, compression ignition (CI) engines, also called diesel engines, will remain of great importance for transportation sectors as well as for power generation in stationary applications in the foreseeable future. In order to promote applications dealing with complex diesel alternative fuels by facilitating their integration in numerical simulation, this paper targets three objectives. First, generate novel diesel fuel surrogates with more than one co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The principle of energy conservation states that the sum of the heat entering the micro-element and the work done on the micro-element by body and surface forces is equal to the rate of energy increase within the micro-element. Equations are as follows [ 37 ]: where e is the specific internal energy in the cylinder, J/kg; h e is the specific enthalpy of the inflow gas, J/kg; h o is the specific enthalpy of the outflow gas, J/kg; Q j is the heat release of fuel, J; p i is the pressure in the cylinder, Pa; V is the working volume, cm 3 ; Q s is the heat loss, J; h u is the specific enthalpy of the leaking gas, J/kg; q o is the fuel latent heat of vaporization, J; f is the fraction by mass of vaporized fuel. Ideal gas equation of state …”
Section: Methodsmentioning
confidence: 99%
“…The principle of energy conservation states that the sum of the heat entering the micro-element and the work done on the micro-element by body and surface forces is equal to the rate of energy increase within the micro-element. Equations are as follows [ 37 ]: where e is the specific internal energy in the cylinder, J/kg; h e is the specific enthalpy of the inflow gas, J/kg; h o is the specific enthalpy of the outflow gas, J/kg; Q j is the heat release of fuel, J; p i is the pressure in the cylinder, Pa; V is the working volume, cm 3 ; Q s is the heat loss, J; h u is the specific enthalpy of the leaking gas, J/kg; q o is the fuel latent heat of vaporization, J; f is the fraction by mass of vaporized fuel. Ideal gas equation of state …”
Section: Methodsmentioning
confidence: 99%
“…In addition to the efforts made to investigate generic or canonical systems, numerical investigations on entropy generation in the RANS framework were also performed in practical systems, such as IC engines [ 118 , 119 , 120 , 121 , 122 ]. Most of the reported numerical studies related to IC engines extend to 3D the methodology referenced above in the experimental investigations [ 37 , 39 , 41 , 43 , 44 , 46 ] mentioned in the previous section dealing with simple exergy or energy balance.…”
Section: Numerical-modeling-based 3d Investigations: Rans-based Model...mentioning
confidence: 99%
“…Recently, Fathi et al [ 121 ] and Mondo et al [ 122 ] also applied the exergy balance within the RANS framework on an IC engine. The first investigation [ 121 ] revealed that the variation of the spray angle in a Reactivity Controlled Combustion Ignition (RCCI) dual fuel engine, fueled by n-heptane, affects the exergy efficiency, which found its maximum value for spray angle between 5° and 20°.…”
Section: Numerical-modeling-based 3d Investigations: Rans-based Model...mentioning
confidence: 99%
See 1 more Smart Citation